SIRT7 regulates hepatocellular carcinoma response to therapy by altering the p53-dependent cell death pathway - Jie Zhao; Ann Wozniak; Abby Adams; Josiah Cox; Anusha Vittal; Jordan Voss; Brian Bridges; Steven A. Weinman; Zhuan Li (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Optimal therapeutic strategies for hepatocellular carcinoma (HCC) patients are still challenging due to the high recurrence rate after surgical resection and chemotherapy resistance. Growing evidence shows that genetic and epigenetic alterations are involved in HCC progression and resistance to therapy, however the molecular mechanisms underlying resistance to therapy have not been fully understood. Methods Expression of SIRT7 in 17 paired paraffin-embedded HCC tissues and adjacent nontumoral liver tissues was examined by immunohistochemistry and Western blot. The mRNA expression of SIRT7 in 20 paired frozen HCC tissues and adjacent nontumoral liver tissues was analyzed by quantitative RT-PCR. The biologic consequences of overexpression and knockdown of SIRT7 in HCC therapy sensitivity were studied in vitro and in vivo. Interaction between SIRT7 and p53 were studied in HCC cell lines. Results SIRT7 expression was frequently upregulated in clinical HCC samples, and its expression was highly associated with TACE-resistance and poor survival (P = 0.008.) Depletion of SIRT7 from multiple liver cancer cell lines significantly increased doxorubicin toxicity while overexpression of SIRT7 largely abolished doxorubicin induced apoptosis. At the molecular level, we observed that SIRT7 interacts with and induces deacetylation of p53 at lysines 320 and 373. Deacetylated p53 showed significantly less affinity for the NOXA promoter and its transcription. In mouse xenografts, SIRT7 suppression increased doxorubicin induced p53 activation, inhibited tumor growth and induced apoptosis. Conclusion The newly identified SIRT7-p53-NOXA axis partially illustrates the molecular mechanism of HCC resistance to therapy and represents a novel potential therapeutic target for HCC treatment.